Menu Dinamis pada Aplikasi Dalam Perspektif Human-Computer Interaction - Armanda, Tubagus Arief; Amin, Ahmad Sakhowi; Wardhani, Ire Puspa (PETIR, 2022)
One part of the interface of an application is the menu. Menus are a common user interface component in many types of applications. Through the menu, the commands of a software (program) are executed to run certain commands from the application. Accessing the menu repeatedly for the same feature is considered ineffective. One of the solutions offered by the researchers is to provide a concept, namely the creation of dynamic menus. This article provides an overview of the dynamic menu concept through several examples of articles from previous researchers